Empowering News Writing Skills: Digital Platforms and Interactive Storytelling in English Broadcasting - Jelita Purnamasari (Jo-ELT (Journal of English Language Teaching) Fakultas Pendidikan Bahasa & Seni Prodi Pendidikan Bahasa Inggris IKIP, 2024)
This study examines the impact of interactive storytelling on improving news writing skills among Communication Science students in an English broadcasting course. Integrating digital platforms with multimedia elements—including audio, video, and graphics—fosters narrative creativity and enhances students' engagement in English news broadcasting. The study involved seven Communication Science students as participants in a qualitative case study, with data collected through news script analysis and interviews. Analysis focused on narrative structure, creativity, and multimedia use, while interviews captured insights into students' experiences and challenges with digital platforms. Using Nvivo 12 software, data analysis revealed significant improvements in students' narrative creativity and multimedia integration. Interactive storytelling techniques improved news script quality and promoted student engagement, independence, and adaptability in learning. Students valued the flexibility and real-time feedback of digital platforms, which allowed experimentation with storytelling techniques and self-paced learning. Despite these benefits, some students encountered challenges related to technical skills and media adaptation. Findings emphasize the value of interactive storytelling in journalism education, with potential applications in professional training for broadcast media, journalism workshops, and multimedia content creation.